The Impact of the Common Core State Standards:The Top Five Shifts in Literacy Instruction - Carolyn Carlson (The Advocate, 2015)
The Common Core State Standards Initiative adopted a goal of having every student in the United States college and career ready by the end of high school. As a result, the CCSS English/Language Arts have influenced the way teachers approach literacy instruction. Since the implementation of the CCSS (or standards similar to the actual CCSS but that vary slightly), there have been five main shifts in literacy instruction. Regardless of grade level, content area, or student characteristics (struggling, gifted, etc.), all instruction is impacted by these five shifts.